Cereals and cereal products: Iron enriched bean and pearl millet grain: Specification - Ganguli, Tora; Walton, Jenny; Pfeiffer, Wolfgang H.; Boy, Erick; Taleon, Victor; Virk, Parminder; Govindaraj, Mahalingam (BSI Standards Limited, 2021)
HarvestPlus leads and coordinates a global effort within the Consultative Group on International Agricultural Research (CGIAR) network to improve nutrition by promoting biofortified, nutrient enriched staple crops. This effort focuses on catalyzing the development, production, delivery and consumption of foods that are rich in essential micronutrients, including vitamin A, iron and zinc. In May 2018, HarvestPlus and GAIN launched a landmark partnership to accelerate progress towards improving access to biofortified seed, grain and foods via commercial channels with the Commercialisation of Biofortified Crops (CBC) programme. The standards outlined in the PAS are meant to enable easier procurement of minimal (postharvest cleaning and removal of agricultural remains) or unprocessed beans and pearl millets at the wholegrain stage in the supply chain. Processing after this point, which may remove part of the grain and reduce micronutrient content, is not covered by this PAS. Further processing and promotion to consumers is not covered.